2019
DOI: 10.1038/s41598-019-49624-w
|View full text |Cite
|
Sign up to set email alerts
|

Production of adeno-associated virus vectors for in vitro and in vivo applications

Abstract: Delivering and expressing a gene of interest in cells or living animals has become a pivotal technique in biomedical research and gene therapy. Among viral delivery systems, adeno-associated viruses (AAVs) are relatively safe and demonstrate high gene transfer efficiency, low immunogenicity, stable long-term expression, and selective tissue tropism. Combined with modern gene technologies, such as cell-specific promoters, the Cre/lox system, and genome editing, AAVs represent a practical, rapid, and economical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 65 publications
1
109
0
Order By: Relevance
“…After the study of additional serotypes, it was reported that the transport of AAV into the media can be highly dependent on serotype, with a majority of AAV expressed in the media for all serotypes except AAV2 and AAV5 (Vandenberghe et al, 2010). Additionally the transport of AAV into media is dependent on expression conditions, such as a mildly alkaline pH or low serum levels (Atkinson et al, 2003;Kimura et al, 2019;Vandenberghe et al, 2010), as well as time post infection/transfection (Piras et al, 2016).…”
Section: Harvest and Clarification Of Aav Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…After the study of additional serotypes, it was reported that the transport of AAV into the media can be highly dependent on serotype, with a majority of AAV expressed in the media for all serotypes except AAV2 and AAV5 (Vandenberghe et al, 2010). Additionally the transport of AAV into media is dependent on expression conditions, such as a mildly alkaline pH or low serum levels (Atkinson et al, 2003;Kimura et al, 2019;Vandenberghe et al, 2010), as well as time post infection/transfection (Piras et al, 2016).…”
Section: Harvest and Clarification Of Aav Cell Culturementioning
confidence: 99%
“…Use of detergents is concentration and time dependent, with reported concentrations of Triton X-100 between 0.1% (2 hr and 37°C; Nass et al, 2018) it poses a potential concern for the downstream impact on chromatographic unit operations exists. The use of acidic buffers for cell lysis, such as citrate at pH 4.2, has also been explored (Kimura et al, 2019;Shuhei Sakamoto et al, 2018) and could prove an alternative to detergents that could mitigate the impact on downstream unit operations as well as the need to show clearance of the additive. Citrate complexes bivalent ions and the low pH may trigger a protease activity of viral capsid proteins that aides with the release of AAV vectors.…”
Section: Harvest and Clarification Of Aav Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This strategy does have advantages over gradient-based purification of intracellular rAAV but still requires large volumes of media and ultracentrifuges that may be cost-prohibitive to smaller laboratories. Another method purifies rAAV from the media via polyethylene glycol precipitation with subsequent aqueous twophase partitioning [48]. This method can be completed without an ultracentrifuge or iodixanol gradient but still requires several additional time-consuming steps such as media changes and incubations with chemical reagents.…”
Section: Discussionmentioning
confidence: 99%
“…In these applications, the GOI replaces the natural AAV genome for delivery to tissues or cells to treat a monogenic disease. In addition, rAAVs are widely used research tools for transgene expression in tissue culture and preclinical animal models ( 18 ).…”
Section: Introductionmentioning
confidence: 99%